Barthes' rhetorical machine: Mythology and connotation in the digital networks - Berrio-Zapata, Cristian [UNESP]; Moreira, Fábio Mosso [UNESP]; Sant'Ana, Ricardo César Gongalves [UNESP] (My University, 2015)
This article explores the social representation of Information Technology and Network Society from Barthes' semiology, using his ideas about myth creation and the connotation of ideological discourses through naturalization. Supplemented with some concepts from Peirce and Santaella, we try to identify and understand these mystification mechanisms and how they affect the creation of an information order; in this case, a digital order. We conclude that we are before an evangelizing discursive alignment based on mythical elements arisen from our aversion to uncertainty, the energy-saving principle, and an engineering discourse guided by the urgency of profit and power. We highlight the presence of a reckless narrative that permanently repeats the urgent need for information technology and digitalization without considering side effects or costs.
Keywords: Barthes; Internet; Peirce; Speech; Technology